Highly Stable Core–Shell Structured Semiconducting Polymer Nanoparticles for FRET‐Based Intracellular pH Imaging. Issue 14 (30th May 2019) - Bao, Biqing; Su, Peng; Yang, Zhenyuan; Zhai, Xue; Zhang, Jingjing; Xu, Yu; Liu, Yunfei; Gu, Bingbing; Wang, Lianhui
Abstract: Highly stable semiconducting polymer nanoparticles (NPs) (poly(9, 9‐dioctylfluorenyl‐2, 7‐diyl) (PFO)/ poly(fluorene‐2, 7‐ylenevinylene‐ co ‐phenylene) (PFV)‐dopamine (DA) NPs) with previously unreported core–shell structure are developed for ratiometric sensing of intracellular pH values. PFO/PFV‐DA NPs comprise central polyfluorene (PFO) as donor and PFV as acceptor, in which the donor and acceptor are spatially separated into the central core and nanoparticle shell. Specifically, thick PFV shells can not only significantly minimize the quenching interference of dopamine on the emission of standard reference (PFO), but are also able to maximize its accessibility to pH‐sensitive dopamine and lead to sensitive response to pH changes. The resulting core–shell PFO/PFV NPs are structurally and optically stable, which can avoid the photobleaching and leakage of materials issues compared to traditional semiconducting polymer nanoparticles (SPNs)‐based fluorescence resonance energy transfer (FRET) systems containing small molecules. Additionally, the designed compact PFO/PFV‐DA NPs show quantitative response to the pH values in aqueous media and are capable of mapping intracellular pH fluctuations by ratiometric imaging. This work may open up opportunities for the generalizability of the consistent ratiometric emission intensity strategy based on core–shell structured SPNs nanoprobes for highly sensitive biological sensing. Abstract : Structurally and optically stable semiconducting polymer nanoparticles (poly(9, 9‐dioctylfluorenyl‐2, 7‐diyl) (PFO)/poly(fluorene‐2, 7‐ylenevinylene‐ co ‐phenylene) (PFV)‐dopamine (DA) nano‐particles (NPs)) with core–shell structure are developed for ratiometric sensing of intracellular pH values. The resulting core–shell PFO/PFV‐DA NPs show quantitative response to the pH values in aqueous media and are capable of mapping intracellular pH fluctuations by fluorescence resonance energy transfer (FRET)‐based ratiometric imaging.